The assessment of interleukin-1 in chronic kidney disease patients with periodontitis following non-surgical periodontal therapy - Kassim, Nur Karyatee; Abdul Rahman, Nurul Aliya; Hanafi, Muhammad Hafiz; Zainuddin, Siti Lailatul Akmar; Kamarudin, Muhammad Imran; Ahmad, Farizan; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Ibrahim, Hanim Afzan; Wan Ahmad, Wan Muhammad Amir (Malaysian Journal Pathology, 2022)
Introduction: Chronic kidney disease (CKD) and periodontitis have an impact on patient’s morbidity and mortality. Periodontitis increases the inflammatory burden, which has been shown to impair renal function by altering serum inflammatory levels. Interleukin-1 (IL-1) has immunomodulatory properties that affect immunological responses of the host. Little is known regarding IL-1 alteration in CKD patients after non-surgical periodontal therapy (NSPT). Therefore, this study was aimed to assess and compare the level of IL-1 at baseline and after receiving NSPT. Materials & Methods: The study included twenty CKD patients with periodontitis (Group 1), twenty non-CKD patients with periodontitis (Group 2) and twenty healthy subjects (Group 3). During each visit, a blood sample was collected and the serum IL-1 concentration was analysed using enzyme-linked immunosorbent assay. Results: Our findings showed that IL-1 level was significantly higher (p<0.05) in Group 1 [Mean (SD) = 0.91(0.39)]pg/ml as compared to Group 2 [Mean (SD)= 0.79(0.27)]pg/ml and Group 3 [Mean (SD) = 0.57(0.39)]pg/ml. Following NSPT, there was significant reduction (p<0.05) in IL-1 level in Group 1 and Group 2. The eGFR has improved from [Mean (SD)= 25.25 (9.93)] mL/min/1.73m2 to 30.3(11.73) mL/min/1.73m2 post NSPT. Discussion: This study found that CKD patients with periodontitis exhibited a more severe systemic inflammatory response than non-CKD patients and healthy subjects. NSPT reduced the inflammatory markers and delay the progression of CKD. IL-1 is a promising inflammatory marker for monitoring CKD progression. Therefore, multicentre and larger sample size studies are needed in the future.